Correctional Executives’ Leadership Self-Efficacy and Their Perceptions of Emotional Intelligence - Harper, Donta S. (American journal of criminal justice, 2016)
Correctional leadership is virtually an unexamined category, lacking literature regarding what is necessary to be a successful correctional executive. This quantitative study involved examining a leadership model of the relationship between emotional intelligence and leader self-efficacy perceptions among correctional executives and senior-level leaders. A convenience sampling of 112 correctional leaders from across the US participated in the study. Participants were asked to complete the WLEIS (Wong & Law Emotional Intelligence Scale) and the Leader Efficacy Questionnaire (LEQ). A correlation and Multivariate Analysis of Variance Analyses (MANOVA) were subsequently conducted. The study findings yielded a statistically significant difference among leaders’ perceptions of their utilization of emotional intelligence and leader self-efficacy in the work environment. The study findings further suggest that gender is predictive across the instrumentation models for this study, with women exhibiting higher levels of emotional intelligence, self-emotional appraisal, use of emotion, leader self-efficacy, and leader self-regulation efficacy.